Blended learning in nursing pharmacology: elevating cognitive skills, engagement and academic outcomes - Hadar Arien-Zakay (Frontiers Media S.A., 2024)
Pharmacological education is crucial for healthcare professionals to safely manage medications and reduce errors. Traditional lecture-based learning (LBL) often struggles to address this complexity, whereas newer methods, such as flipped classrooms and problem-based learning, yield mixed results, particularly in pre-clinical contexts, owing to students' limited experience. Our nursing pharmacology course under LBL recorded a high failure rate of 37.8% and marginal passing scores across five cohorts (n = 849 students). An analysis using Bloom's taxonomy revealed significant gaps in higher-order cognitive skills. As a remedy, the course was transformed into a novel blended learning format that integrated question-based learning (QBL) to enhance critical thinking across all cognitive levels. This model blends asynchronous and synchronous learning, is tailored to individual needs in large classes, and fosters continuous, student-centric learning. The redesign markedly decreased the failure rate by approximately 2.8-fold and increased the average grade by 11.8 points among 426 students. It notably improved the pass rates in advanced cognitive categories, such as "Evaluate" and "Create" by 19.0% and 24.2%, respectively. Additionally, the blended course showed increased student engagement, reflecting a dynamic and effective learning environment that significantly elevated participation and academic outcomes at all cognitive levels. This study demonstrated the profound impact of blended learning in pharmacology. By integrating QBL with various teaching methods, it surpasses traditional lecture-based limitations, enhancing engagement and understanding of complex topics by nursing students. Notable improvements in foundational and advanced learning suggest its broader application in health professionals' education, effectively equipping students for clinical pharmacology challenges.